2021
DOI: 10.4103/jfmpc.jfmpc_731_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and knowledge of hepatitis B infection in pregnant women in a primary health center of Patna district, Bihar

Abstract: Introduction: There is a risk of chronic hepatitis B virus (HBV)infection to the newborn through perinatal transmission from a hepatitis B surface antigen (HBsAg) positive mother that can later cause liver cirrhosis or hepatocellular carcinoma. This study was undertaken in a primary health center (PHC)in the Patna district to determine the prevalence of HBV among pregnant women and assess their knowledge across different characteristics. Methodology: A cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…This is not surprising given that most material for education on hepatitis B is usually print which only more educated women can read. The study by Pandey et al, in India also reported level of education as a significant determinant of pregnant women's knowledge on hepatitis B [19]. Single women also had Pregnant Women in the Loum Health District, Cameroon significantly higher knowledge compared to Married women in our study.…”
Section: Discussionsupporting
confidence: 70%
“…This is not surprising given that most material for education on hepatitis B is usually print which only more educated women can read. The study by Pandey et al, in India also reported level of education as a significant determinant of pregnant women's knowledge on hepatitis B [19]. Single women also had Pregnant Women in the Loum Health District, Cameroon significantly higher knowledge compared to Married women in our study.…”
Section: Discussionsupporting
confidence: 70%